Seminar on mergers and acquisition : Stimulating corporate growth and survival through mergers and acquisitions - Securities and Exchange Commission; Association of Issuing Houses of Nigeria (Nigeria: Securities and Exchange Commission, 2003)
The book comprises five (5) different paper presentations on mergers and acquisition.
rua 24/11/16
Loans
Keywords: Mergers and acquisitions; Consolidation and merger of corporations; Corporate reorganization